Heritability estimates for weight gain in Nellore in Mato Grosso state, using model of infinite dimension - D. A. Palharim D. A. Palharim; C. V. Araujo; T. C. B. S. C. Bittencour; S. I. Araujo; L. A. F. Bezerra (Scientific Electronic Archives, 2013)
Abstract: We used 138,976 records of information of body weights ranging from 60 to 610 days of age, from 27,327 Nelore cattle of herds in the state of Mato Grosso. The random regression model with the covariance function of fourth order to describe the variability of the effects of additive genetic, animal and maternal permanent environment and maternal genetic effect and maternal, showed heritability estimates from 0.209 to 0.423 at the beginning by the end of the trajectory, respectively. There is enough genetic variability to promote genetic gain satisfactory performance for weight after weaning period the animals. Keywords: beef cattle, genetic parameters, selection.